Thinking "outside the box": The effect of nontarget snails in the aquatic community on mollusc-borne diseases - Stanicka, Anna; Cichy, Anna; Bulantová, Jana; Labecka, Anna Maria; Ćmiel, Adam Marcin; Templin, Julita; Horák, Petr; Żbikowska, Elżbieta (The Science of the total environment, 2022)
There is a great need to understand the impact of complex communities on the free-living parasite stages that are part of them. This task becomes more complex as nonnative species emerge, changing existing relationships and shaping new interactions in the community. A relevant question would be: Can the coexistence of nontarget snails with the target hosts contribute to trematodasis control? We used field and experimental approaches to investigate nonnative competitor-induced parasite dilution. During a three-year field study, we investigated digenean infection in Lymnaea stagnalis from eight Polish lakes inhabited or uninhabited by Potamopyrgus antipodarum. Additionally, we verified the presence of digenean infections in the populations of P. antipodarum. Moreover, we conducted an experimental infection of L. stagnalis with miracidia of Trichobilharzia szidati under increasing densities of P. antipodarum and aimed to infect P. antipodarum with them separately. The prevalence of avian schistosomes in lymnaeid snails was significantly higher in uninhabited lakes than in lakes inhabited by P. antipodarum. Our study indicates that waters with a higher density of invaders have a lower prevalence of avian schistosomes in lymnaeid hosts. The results of experimental studies confirmed that the presence of high densities of P. antipodarum reduces the probability of target host infection. Both field and experimental studies rule out the role of P. antipodarum as a source of avian schistosome cercariae. Here, a nonnative species was tested as a diluter, which in practice may be harmful to the local environment. This work is not a call for the introduction of nonnative species; it is intended to be a stimulus for researchers to continue searching for natural enemies of parasites because, as our results show, they exist. Finding natural enemies to the most dangerous species of human and animal parasites that will pose no threat to the local environment could be groundbreaking.
Keywords: Dilution effect; Lymnaea stagnalis; jezera; Potamopyrgus antipodarum; Lymnaea; hlemýždi; Animals; Cercaria; Humans; lidé; Trichobilharzia szidati; Lakes; zvířata; Miracidia; cerkárie; Snails; Schistosomatidae; Cercarial dermatitis